Applications of Multi-Criteria and Game Theory Approaches Manufacturing and Logistics - Benyoucef, Lyes (Springer Series in Advanced Manufacturing, 2014)
Aligning the latest practices, innovations and case studies with academic frameworks and theories, the broad area of multi-criteria and game theory applications in manufacturing and logistics is covered in comprehensive details. Part 1 presents â_~multi-criteria applicationsâ_T and includes chapters onÂ  logistics with a focus on vehicle routing problems, a multi-objective decision making approach to select the best storage policy and an exploratory study to predict the most important factors that can lead to successful mobile supply chain management adoption for manufacturing firms. PartÂ 2 covers â_~game theory applicationsâ_T and encompasses the process of forming a coalition within a corporate network to the problem of integrating inventory and distribution optimization together with game theory to effectively manage supply networks. Providing a forum to investigate, exchange novel ideas and disseminate knowledge covering the broad area of multi-criteria and game theory applications in manufacturing and logistics, Applications of Multi-Criteria and Game Theory Approaches is an excellent reference for students, researchers,Â and managers and industry professionals working with manufacturing and logistics issues.